Continuity and change in Ciskei chiefship - Peires, J.B. (My University, 1977)
The conventional wisdom of South African ethnologists, whether liberal or conservative, has been dominated by the idea that African politics operated according to certain fixed rules ("customs") which were hallowed by tradition and therefore never changed. A corollary of this is that if these rules were correctly identified and fairly applied, everyone would be satisfied and chiefship could perhaps be saved. It is, however, fairly well established that genealogies are often falsified, that new rules are coined and old rules bent to accommodate changing configurations of power, and that ‘age-old’ customs may turn out to be fairly recent innovations; in short, that "organisational ideas do not directly control action, but only the interpretation of action". The conventional wisdom was successfully challenged by Comaroff in his important article, ‘Chiefship in a South African Homeland’, which demonstrated that by adhering too closely to the formal features of traditional government and politics among the Tswana, especially those concerning succession, the Government wrecked the political processes which had enabled the Tswana to choose the most suitable candidate as chief. And yet Comaroff’s article begs a good many questions. Let us imagine that the Government ethnologists read the article, and as a result allow Tswana chiefs to compete for office as before, permitting "consultative decision-making and participation in executive processes". Would this prevent the Tswana chiefship from dying? Can we, in fact, discuss chiefship in political terms alone without considering whether the material conditions in which it flourished still exist? The present article will attempt to situate the question of chiefship in a somewhat wider framework than that usually provided by administrative theory or transactional analysis.
African Studies Seminar series. Paper presented August 1977
Keywords: Xhosa (African people). Kings and rulers; Ciskei (South Africa). Kings and rulers; Ciskei (South Africa). Politics and government